Dyadic neuroscience is the next scientific frontier of sociocognitive development: a proof-of-concept for a collaborative conversation task in clinical and underrepresented populations - Nelson, Cailee M.; Wilson, Sarah C.; McFadden, Jackson; Almor, Amit; Hudac, Caitlin M. (Frontiers in Developmental Psychology, 2025)
Developmental cognitive neuroscience studies the evolution of the bidirectional links between biology and cognition during development. An area of recent focus is the impact of social factors on the biology-cognition link. Indeed, recent calls-to-action encourage a more dynamic approach to investigating mechanisms related to the development of the social brain. To address this need, we utilized a burgeoning innovation in cognitive neuroscience known as “hyperscanning”, which allows for real-time synchronized measurements of biological signals (e.g., brain signals via electroencephalography, EEG; cardiac activity via electrocardiogram, ECG) across two people engaged in social interaction. The potential of hyperscanning has yet to be tapped for research with diverse and developmental populations underrepresented in neuroscience (and science broadly), including pediatric clinical and racial minority populations. The present manuscript provides proof-of-concept for the use of naturalistic and inclusive hyperscanning paradigms. For this research, we adapted a collaborative conversation task that allowed us to examine differences in synchronized measures of sociocognitive mechanisms (specifically, motivation and language) across different social contexts (familiar child dyads, stranger child dyads, familiar adult-child dyads, and stranger adult dyads). Preliminary results from a pilot study with 45 racially diverse autistic and non-autistic participants indicate that, at the group level, youth are less accurate and need more hints than adults, peer dyads (i.e., child-child, adult-adult) are more approach-motivated, and dyad features (e.g., familiarity) influence how linguistically aligned individuals are during the task. Additionally, we provide initial evidence for within-person biology-behavior links and asymmetrical between-person alignment of approach motivational brain states that indicate that one's current motivation state was predicted to be opposite of their partner and vary subtly across social contexts. Overall, this hyperscanning task is sensitive to developmental and contextual factors and will propel our understanding of social and cognitive processes. We encourage cognitive developmentalists to consider recommendations laid out in the current proof-of-concept to take actionable steps in moving the field toward more inclusive and pervasive research.